Behavior of Hydrogen and Nitrogen in Tungsten, as Divertor Wall of a Fusion Reactor - Beneitez, Sergio (2018)
The analysis of the interaction of hydrogen, nitrogen (and their isotopes) with tungsten is important, since this material is a strong candidate to form the first wall of fusion reactors for both magnetic and inertial confinement, and these atoms have a very sensitive (desired and unwanted) interaction with it. For this purpose, we study the effects and electronic state densities of atomic hydrogen and nitrogen in pure tungsten, in order to analyze some important properties such as the density of states of the system. Focusing on this application, this work is a preliminary study of the behavior of atoms of hydrogen and nitrogen, on a surface of tungsten on the three sites of the cell: top, hollow and bridge. We use a program simulation based on the DFT (density functional theory) implemented in the Open-Source Code Quantum Espresso, in order to obtain the adsorption energy and the density of states of the systems.